The Role of Computers in Philosophy: An Interaction Perspective Humans and Technology - Manan, Abdul; Kodrat, Hikmat; Rimasa, Dery (Jurnal Ilmiah Mandala Education (JIME), 2025)
The development of computers has brought profound changes to human thinking and the philosophy of existence, knowledge, and social interaction. This research aims to examine the role of computers in a philosophical perspective, especially in the context of human interaction with technology. The method used is a literature review model, with articles that have gone through a screening process to strengthen the study. The results show that computers are not just technical tools, but function as epistemic agents and mediators of human reality. The development of this technology raises new implications in the philosophy of consciousness, ethics, and human existence.